The political mind : why you can't understand 21st-century politics with an 18th-century brain - Lakoff, George (New York : Viking, 2008)
In What's the Matter with Kansas?, Thomas Frank pointed out that a great number of Americans actually vote against their own interests. In The Political Mind, George Lakoff explains why.
Introduction : brain change and social change -- How the brain shapes the political mind -- Anna Nicole on the brain -- The political unconscious -- The brain's role in family values -- The brain's role in political ideologies -- Political challenges for the twenty-first-century mind -- A new consciousness -- Traumatic ideas : the War on Terror -- Framing reality : privateering -- Fear of framing -- Confronting stereotypes : sons of the welfare queen -- Aim above the bad apples -- Cognitive policy -- Contested concepts everywhere -- The technical is the political -- Exploring the political brain -- The problem of self-interest -- The metaphors defining rational action -- Why hawks win -- The brain's language -- Language in the new enlightenment -- Afterword : what if it works? -- Acknowledgments -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Liberalism -- United States; Progressivism (United States politics); Political culture -- United States; Conservatism -- United States; Communication in politics -- United States; Thought and thinking